Incorporation of thio-pseudoisocytosine into triplex-forming peptide nucleic acids for enhanced recognition of RNA duplexes - Devi, Gitali (2014)
Peptide nucleic acids (PNAs) have been developed for applications in biotechnology and therapeutics. There is great potential in the development of chemically modified PNAs or other triplex-forming ligands that selectively bind to RNA duplexes, but not single-stranded regions, at near-physiological conditions. Here, we report on a convenient synthesis route to a modified PNA monomer, thio-pseudoisocytosine (L), and binding studies of PNAs incorporating the monomer L. Thermal melting and gel electrophoresis studies reveal that L-incorporated 8-mer PNAs have superior affinity and specificity in recognizing the duplex region of a model RNA hairpin to form a pyrimidine motif major-groove RNA2–PNA triplex, without appreciable binding to single-stranded regions to form an RNA–PNA duplex or, via strand invasion, forming an RNA–PNA2 triplex at near-physiological buffer condition. In addition, an L-incorporated 8-mer PNA shows essentially no binding to single-stranded or double-stranded DNA. Furthermore, an L-modified 6-mer PNA, but not pseudoisocytosine (J) modified or unmodified PNA, binds to the HIV-1 programmed −1 ribosomal frameshift stimulatory RNA hairpin at near-physiological buffer conditions. The stabilization of an RNA2–PNA triplex by L modification is facilitated by enhanced van der Waals contacts, base stacking, hydrogen bonding and reduced dehydration energy. The destabilization of RNA–PNA and DNA–PNA duplexes by L modification is due to the steric clash and loss of two hydrogen bonds in a Watson–Crick-like G–L pair. An RNA2–PNA triplex is significantly more stable than a DNA2–PNA triplex, probably because the RNA duplex major groove provides geometry compatibility and favorable backbone–backbone interactions with PNA. Thus, L-modified triplex-forming PNAs may be utilized for sequence-specifically targeting duplex regions in RNAs for biological and therapeutic applications.